Optimizing Memory Usage in L4-Based Microkernel - Eftime, Petre; Mogoşanu, Lucian; Carabaş, Mihai; Deaconescu, Răzvan; Gheorghe, Laura; Voiculescu, Valentin Gabriel (Computing and Informatics, 2017)
Memory allocation is a critical aspect of any modern operating system kernel because it must run continuously for long periods of time, therefore memory leaks and inefficiency must be eliminated. This paper presents different memory management algorithms and their aplicability to an L4-based microkernel. We aim to reduce memory usage and increase the performance of allocation and deallocation of memory.